2009
DOI: 10.1111/j.1742-4658.2009.07247.x
|View full text |Cite
|
Sign up to set email alerts
|

Purine nucleoside phosphorylases from hyperthermophilic Archaea require a CXC motif for stability and folding

Abstract: 5′‐Deoxy‐5′‐methylthioadenosine phosphorylase II from Sulfolobus solfataricus (SsMTAPII) and purine nucleoside phosphorylase from Pyrococcus furiosus (PfPNP) are hyperthermophilic purine nucleoside phosphorylases stabilized by intrasubunit disulfide bonds. In their C‐terminus, both enzymes harbour a CXC motif analogous to the CXXC motif present at the active site of eukaryotic protein disulfide isomerase. By monitoring the refolding of SsMTAPII, PfPNP and their mutants lacking the C‐terminal cysteine pair afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Deletion of one AA to form a CXC motif in E. coli thioredoxin greatly increases the disulfide isomerase activity, and even a synthetic CXC tripeptide possesses such activity (52). In addition, the presence of a CXC motif at the C terminus of two enzymes from hyperthermophilic Archaea was shown to be necessary for folding of these enzymes (53), and in their absence, the addition of synthetic peptides, containing the CXC region, was able to restore the folding. These peptides were also shown to have disulfide isomerase activities (53).…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of one AA to form a CXC motif in E. coli thioredoxin greatly increases the disulfide isomerase activity, and even a synthetic CXC tripeptide possesses such activity (52). In addition, the presence of a CXC motif at the C terminus of two enzymes from hyperthermophilic Archaea was shown to be necessary for folding of these enzymes (53), and in their absence, the addition of synthetic peptides, containing the CXC region, was able to restore the folding. These peptides were also shown to have disulfide isomerase activities (53).…”
Section: Discussionmentioning
confidence: 99%
“…Each subunit is stabilized by two pairs of intramolecular disulfide bonds and shows in its C‐terminal region an unusual CXC motif as a typical feature [Cacciapuoti et al, ; Zhang et al, ]. By enzymatic activity measurements, it has been demonstrated that this unusual disulfide plays a specific stabilizing role by acting as a redox reagent in restoring the native state of reduced or scrambled structural disulfide of the enzyme [Cacciapuoti et al, , ]. The hexamer of SsMTAPII, consisting of a dimer‐of‐trimers with one active site per monomer, is considerably different from the hexamer of SsMTAP and fits more closely with members of the trimeric class of PNPs [Zhang et al, ].…”
Section: Resultsmentioning
confidence: 99%